Trichoderma tlahuicanensis sp. nov. (Hypocreaceae), a novel mycoparasite of Fusarium oxysporum and Phytophthora capsici isolated from a traditional Mexican milpa - Iza-Arteaga, Mario; Lira-Ruan, Verónica; Balcázar-López, Edgar; Folch-Mallol, Jorge Luis; Sánchez-Reyes, Ayixon (Frontiers in Microbiology, 2025)
IntroductionThe genus Trichoderma encompasses cosmopolitan fungi that play key ecological and biotechnological roles, including mycoparasitism, plant growth promotion, and tolerance to abiotic stress. As the catalog of undescribed species continues to expand, the need for precise species delimitation is increasingly evident.MethodsIn this work, we isolated strain BMH-0061 as a root endophyte of chili (Capsicum annuum) and assessed its phenotypic and antagonistic potential. This strain originated from Mexico’s milpa agroecosystem, an underexplored reservoir of microbial diversity. To robustly evaluate its taxonomic status, we generated a near-complete, telomere-to-telomere genome assembly and assessed its completeness with BUSCO. Subsequently, we evaluated a comprehensive set of genomic coherence metrics, including Average Nucleotide Identity (ANI), Average Amino Acid Identity (AAI), Percentage of Conserved Proteins (POCP), and k-mer composition.ResultsIntegrative phylogenomic analyses, supported by Bayesian speciation models and clustering-based comparisons, consistently recovered BMH-0061 as an independent lineage. The strain exhibited broad-spectrum mycoparasitism against phytopathogens and tolerance to moderate abiotic stress. Morphological characterization, growth profiles, and multi-gene phylogenies suggested its placement within the Trichoderma genus, but it is distinct from known species. A near-complete telomere-to-telomere genome assembly was obtained, showing a BUSCO completeness of 99.08%. Genomic coherence analyses revealed that strain BMH-0061 shared ANI values ranging from 83.93% to 94.43% with its closest Trichoderma relatives, supporting its distinction as a separate lineage.DiscussionWe formally describe this new taxon as Trichoderma tlahuicanensis sp. nov., in honor of the indigenous pre-Hispanic Tlahuica people of Morelos, Mexico. Our work demonstrates how a phylophenetic framework, combining genomic, phylogenetic, genetic diversity, and evolutionary analyses, provides a powerful approach to species delimitation. This integrative strategy confirms the recognition of T. tlahuicanensis as a distinct species while offering a methodological pathway for peers engaged in fungal systematics